Geographical Variation of Diet Composition of Cervus nippon kopschi in Jiangxi, China Based on DNA Metabarcoding - Xiao Sun; Feiyan Lv; Xueqin Hu; Jun Tian; Ruijie Yang; Jie Yao; Zhiqiang Huang; Jiancheng Zhai (Animals)
Food resources are the fundamental basis for the survival and reproduction of animals. Diet research is the foundation for understanding their ecological habits and is of great significance for evaluating their survival status and carrying out effective protection and management. South China sika deer (Cervus nippon kopschi) is the most endangered subspecies of wild sika deer in China, with a small population and a shrinking distribution area. Here, we used DNA metabarcoding technology to study the diet composition of C. n. kopschi in Taohongling Sika Deer National Nature Reserve in Jiangxi, China. Comparative analysis of diet composition among different areas (A–E) of C. n. kopschi was conducted, as well as C. n. hortulorum raised in the same areas. We found that the dominant families in the diet composition of C. n. kopschi were Rosaceae (46.73% of relative abundance), Anacardiaceae (6.02%), Poaceae (5.54%), and Fabaceae (3.92%), with Rubus (45.43%) being the absolute dominant genus. Thirty-two preferred plant species were identified in the diet of C. n. kopschi. The highest relative abundance (45%) was Rubus reflexus. The dominant family and genus in the diet composition of C. n. hortulorum were Fabaceae (33.89%) and Pueraria (32.87%), respectively. Of the 15 preferred plant species, the highest relative abundance was Pueraria montana (33%). The richness, diversity, and evenness of diet composition in Area B of C. n. kopschi were the highest among all areas, with significant differences compared to Areas C, D, and E. Diet composition of deer in Area A did not differ significantly from those in other areas. Principal coordinate analysis (PCoA) and nonmetric multidimensional scaling (NMDS) both indicated a significant separation in the diet composition of C. n. kopschi and C. n. hortulorum, while Area B showed significant separation from the other areas. This study elaborates on the diet composition information of C. n. kopschi and can provide a reference for the protection and improvement of the habitat of sika deer.